The successional trajectory of bacterial and fungal communities in soil are fabricated by yaks’ excrement contamination in plateau, China - Shang, Zhenda; Wang, Yaping; An, Miao; Chen, Xiushuang; Kulyar, Muhammad Fakhar-e-Alam; Tan, Zhankun; Liu, Suozhu; Li, Kun (Frontiers in Microbiology, 2022)
The soil microbiome is crucial in determining contemporary realistic conditions for future terrestrial ecological and evolutionary development. However, the precise mechanism between the fecal deposition in livestock grazing and changes in the soil microbiome remains unknown. This is the first in-depth study of bacterial and fungal taxonomic changes of excrement contaminated soils in the plateau (> 3500 m). This suggests the functional shifts towards a harmful-dominated soil microbiome. According to our findings, excrement contamination significantly reduced the soil bacterial and fungal diversity and richness. Furthermore, a continuous decrease in the relative abundance of microorganisms was associated with nutrient cycling, soil pollution purification, and root-soil stability with the increasing degree of excrement contamination. In comparison, soil pathogens were found to have the opposite trend in the scenario, further deteriorating normal soil function and system resilience. Such colonization and succession of the microbiome might provide an important potential theoretical instruction for microbiome-based soil health protection measures in the plateau of China.